Causal modelling between human capital and firm performance indicators: an IT industries' perspective. (2017) - Sekhar, Chandra; Patwardhan, Manoj; Vyas, Vishal
In a knowledge-based economy, Human Capital (HC) is the most important asset. It represents knowledge, skills, experience and capabilities of the employees. The present study utilised standardised scale of HC. Simultaneously, the firm performance scale was adapted from previous researches of respective domains. Database was accumulated from the IT firms that deal in the software development and integration, consultancy, maintenance services to banking industries, manufacturing and other domains of leading national and multi-national IT firms operating in India. The measurement model is a Confirmatory Factor Analysis. Reliability of the construct was reported under acceptable range, and the regression weights were significant. All observed variables loaded to their corresponding first-order construct. In the end, causal relations were analysed through DEMATEL (Decision-Making and Trial Evaluation Laboratory) methodology. Direct-relation matrix is obtained for all the criteria of HC and firm performance and finally, the degree of impact graph is obtained.